2021
DOI: 10.1002/cphc.202000988
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Influence of Electrical Potentials on the Formation of Charged Oligopeptide Self‐Assembled Monolayers on Gold

Abstract: Self‐assembled monolayers (SAMs) based on oligopeptides have garnered immense interest for a wide variety of innovative biomedical and electronic applications. However, to exploit their full potential, it is necessary to understand and control the surface chemistry of oligopeptides. Herein, we report on how different electrical potentials affect the adsorption kinetics, stability and surface coverage of charged oligopeptide SAMs on gold surfaces. Kinetic analysis using electrochemical surface plasmon resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Other studies have observed increases in packing density of a thioctic acid derivative when negative potentials were applied and suggested a potential-dependent surface reaction with no electron transfer was occurring 36 . Interestingly, in a highly related study of the adsorption of cysteine-terminated positively charged oligopeptides under similar AEF conditions (between − 0.4 V and + 0.3 V vs. Ag/AgCl) in PBS, the AEF had no impact on packing density 42 . Since our study is carried out in DI water instead of PBS, higher water coverage on the surface could cause some of the difference in adsorption behavior seen between this and the aforementioned work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have observed increases in packing density of a thioctic acid derivative when negative potentials were applied and suggested a potential-dependent surface reaction with no electron transfer was occurring 36 . Interestingly, in a highly related study of the adsorption of cysteine-terminated positively charged oligopeptides under similar AEF conditions (between − 0.4 V and + 0.3 V vs. Ag/AgCl) in PBS, the AEF had no impact on packing density 42 . Since our study is carried out in DI water instead of PBS, higher water coverage on the surface could cause some of the difference in adsorption behavior seen between this and the aforementioned work.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that the negative potential forces the (−)charged C-terminus to be oriented away from the gold surface while the cysteine-attached N-terminus is in contact with the gold surface. Electric fields have been shown to impact molecular orientation in simulations of alkanethiols on gold 45 , as well as experiments with charged oligopeptides 42 , 43 , 53 , 54 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations